PENGEMBANGAN MODEL EVALUASI PROGRAM LAYANAN PENDIDIKAN ANAK USIA DINI (PAUD) - Gunartha, I Wayan; Kartowagiran, Badrun; Suardiman, Siti Partini (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2014)
Penelitian ini bertujuan: (1) mengembangkan model evaluasi program layanan PAUD (TK kelompok B) dan (2) menilai keefektifan model yang dikembangkan. Penelitian ini merupakan research and development. Subjek coba adalah guru dan siswa TK kelompok B. Instrumen pengumpul data adalah kuesioner dan lembar observasi. Uji coba dilakukan 3 tahap dengan jumlah subjek meningkat setiap tahapnya. Analisis validitas kuesioner menggunakan exploratory factor analysis dan cofirmatory factor analysis (CFA). Estimasi reliabilitas kuesioner tingkat perkembangan anak dan life skills menggunakan CFA dengan menghitung composite reliability. Estimasi reliabilitas kuesioner kompetensi guru dan fasilitas menggunakan teknik Alpha. Estimasi reliabilitas lembar pengamatan dengan dua orang pengamat menggunakan teknik Kappa. Hasil penelitian berupa model evaluasi program layanan PAUD (Model IPPO), yang terdiri atas prosedur, panduan evaluasi, dan instrumen-instrumennya yang cukup baik. Berdasarkan uji coba, semua instrumen memiliki kecocokan model yang baik (fit), validitas konstruk, dan reliabilitas yang memenuhi persyaratan akademik. Menurut penilaian para praktisi dan pengguna model, model IPPO sangat efektif untuk diterapkan.Kata kunci: pengembangan, model evaluasi, pendidikan anak usia dini______________________________________________________________DEVELOPING A PROGRAM EVALUATION MODEL OF EARLY CHILDHOOD EDUCATION (ECE) SERVICEAbstract The study was to: (1) develop an evaluation model of early childhood education (Group-B Kindergarten); and (2) evaluate the effectiveness of the model being developed. The study is a research and development one. The subject of the research was the teachers and the students of Group-B Kindergarten. The data gathering instruments were questionnaires and observational sheet. The experiment was performed in 3 stages with increasing number of participants for each stage. To analyze the questionnaire's validity, the researchers employed exploratory factor analysis and confirmatory factor analysis (CFA).To estimate the reliability of the questionnaire of the children's developmental stage and life skills, the researchers employed CFA by calculating the composite reliability. To estimate the reliability of the questionnaire's of the teacher competence and the facility, the researchers employed Alpha technique. For the estimation of reliability toward the observational sheet with two observers the researchers employed Kappa technique. The result of the research was a model of evaluation of the early childhood education (IPPO Program), consisting of procedures, evaluation guideline and the well-designed instruments. Based on the experiment, all of the instruments have had a goodness of fit (fit), construct validity and reliability that meet all of the academic requirements. According to the evaluation from the practitioners and the model users, the IPPO model is very effective to be implemented.Keyword: development, evaluation model, early childhood education.